Konsep Tanggungjawab Siswa Sekolah Dasar (SD/MI) dalam Perspektif Teori Tindakan Sosial Max Weber - Tamba, Tina Melinda; Shaleh, Shaleh (Program Studi Pendidikan Guru Madrasah Ibtidaiyah (PGMI) Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH) Lamongan, 2024)
This inquires about points to analyze the social activities of elementary/MI understudies with respect to understudy obligations utilizing Max Weber's concept of social activity. The sort of inquire about utilized is writing consider in information administration. The information sources for this investigate are different book references, diaries and/or other pertinent sources. The discoveries of this investigate are social activity utilizing Max Weber's hypothetical approach as a reference for how and why understudies carry out obligations at school with different thought processes with the point of shaping positive understudy character and behavior, as well as creating freedom and teach in learning. The conclusion gotten by this investigate is that Max Weber includes a subjective social procedure and approach which is actualized in understudies, to be specific that their discernment, meaning of cleanliness, activities and conventional variables have a vital part in their handle of carrying out these propensities.